PERANAN OTORITAS JASA KEUANGAN DALAM MENGAJUKAN PERMOHONAN PAILIT PERUSAHAAN ASURANSI (Studi Kasus Perusahaan Asuransi PT.Bumi Asih Jaya) - Eri Lukmanul Hakim Pulungan; Bismar Nasution; Sunarmi Sunarmi; Mahmul Siregar (USU LAW JOURNAL, 2018)
ABSTRACT   The existence of authority in filing an application for bankruptcy declaration for a centralized insurance company in one institution, namely the Minister of Finance which is then transferred to the Financial Services Authority increasingly makes the problem more complex related to legal protection for its customers. The absence of authority in submitting an application for bankruptcy statement to the insurance company will make the client feel insecure when investing in the insurance company. For insured users (insured or insurance customers), the bankruptcy process of a company is one way of debt collection, in addition to various other means of debt collection known by law, such as billing through a bond, the execution of debt guarantees, or bills through court procedures with ordinary procedures. There is a different interpretation between the law and the judge who decides the bankruptcy case of the company. The judge in his verdict states that the company declared bankrupt must be requested by another person or company concerned or the company that feels aggrieved whereas in the Insurance Insurance Act and the Laws of the Financial Services Authority itself states that the Financial Services Authority is authorized to bankrupt the insurance company as appropriate with the purpose of establishing its own Financial Services Authority to regulate and supervise the activities of financial services in the capital market sector. There is a difference of interpretation between judges and the law. It is important to do research on how the role of Financial Services Authority in applying for insolvency insurance company. Keywords: Financial Services Authority, Insolvency, Insurance Company.